The effects of microwave radiation on rumen degradation characteristics of barley straw cut at two different stages of maturity - Asmuddin Natsir (Indonesian Center for Animal Research and Development (ICARD), 2007)
A common approach for improving the nutritive value of low quality roughages and crop by-products is by pre-treatment or processing either physical, chemical, or biological treatments. Microwave radiation is one type of physical treatment that could be used to treat low quality roughages. Research was carried out to investigate the effects of microwave radiation on the rumen degradation characteristics of barley straw obtained from two different stages of maturity. The experiment was run factorially based on completely randomized block design. The first factor was stage of maturity, straw cut during the soft elongation time (C1) and during the harvest time (C2). The second factor was levels of microwave radiation times (MWRT) (T0 = control, without MWR; T1 = MWR for 1 minute, T2 = MWR for 2 minutes). The results indicated nutritive values of barley straw obtained from C1 sampling time were significantly better than that obtained from the C2 sampling time in terms of a higher rumen degradation rate and a much greater total potential rumen degradability. In contrast, MWR did not have significant effects on the rate of degradation and total potential degradability of straw in the rumen. Key Words: Microwave Radiation, Barley Straw, Rumen Degradability